Revolusi dan Inovasi Model Pembelajaran Pendidikan Agama Kristen Yang Efektif Dalam Perspektif Paulo Freire - Sensius Amon Karlau; Ivo Sastri Rukua (JURNAL LUXNOS, 2022)
Abstract:Paulo Freire gave his ideas in the field of education, which also influenced the praxis of education at various families, stages, levels, types, and objectives, including Christian religious education. In his argument, Freire rejects the wrong and oppressive education pattern with the slogan "Pedagogy of the Oppressed" oriented to the banking method pattern. If so, how to understand the revolutionary and innovative learning model of Christian religious education from Paulo Freire's perspective? The author uses a qualitative method with a library research approach. It is understood that the revolution and innovation of learning in Christian religious education should continue to be echoed and, as far as possible, packaged and connected to the context of actual problems in people's lives simultaneously, which leads to the call to "liberate." This effort indeed leads to the quality of graduates who can compete in various competitions now and in the future. So the revolutionary and innovative learning model in Christian religious education in Freire's perspective always emphasizes freedom, and the learning model is patient in dealing with actual problems and dares to hold back against various inequalities in a positive way through dialogue and dares to make positive changes for optimal results. Abstrak: Paulo Freire memberikan gagasannya dalam bidang pendidikan yang turut mempengaruhi praksis pendidikan pada berbagai rumpun, tingkat, jenjang, jenis dan tujuannya, termasuk pendidikan agama Kristen. Dalam argumentasinya, Freire menolak pola pendidikan yang salah dan bersifat menindas dengan slogan “Pedagogi of the Oppressed” yang berorientasi pada pola banking method. Jika demikian, bagaimana memahami revolusi dan inovasi model pembelajaran pendidikan agama Kristen dalam perspektif Paulo Freire? Penulis menggunakan metode kualitatif dengan pendekatan kepustakaan (library research). Maka dipahami bahwa revolusi dan inovasi pembelajaran pendidikan agama Kristen sebaiknya terus dikumandangkan dan sedapat mungkin dikemas dan dihubungkan dengan konteks persoalan aktual dalam kehidupan masyarakat secara simultan yang mengarah pada panggilan “membebaskan”. Upaya ini tentunya bermuara pada mutu lulusan yang mampu bersaing dalam berbagai persaingan pada masa kini maupun ke depan. Maka model pembelajaran pendidikan agama Kristen revolusionis dan inovatif dalam perspektif Freire selalu menekankan aspek kebebasan, sabar menghadapi berbagai persoalan aktual dan berani menahan diri terhadap berbagai ketimpangan secara positif melalui dialog serta berani melakukan perubahan ke arah yang positif untuk hasil yang optimal.